Mid-span hollow foam concrete beam - Nurul Azuan, Mohamed Yusof (2014)
In the design of elevated precast concrete slab, hollow section is often adopted in order to reduce the selfweight of precast slab. With that idea, this project proposed hollow beams made of foam concrete and the investigate the performance of beams in terms of deflection, cracking, and strain. An experimental program including a solid foam concrete beam and 4 hollow foam concrete beams with different area of hole were tested under monotonic four point loading until ultimate physical failure. The dimension of beam is 0.15 x 0.2 x 3.0 m. The beam was simply supported during test with use the roller support. The results of performance for a solid beam and the hollow beams were compared in term of deflection, cracking, and strain. The strain gauge and linear variable displacement transducer (LVDT) were used to determine the strain and deflection of beam, respectively. From this experiment, the result show that the shear failure were occurred on the foam concrete beam. Therefore, the shear reinforcement or link need to be rectified. The hollow beam able to withstand until to the design load but will produce more deflection compare to a solid beam. However, the deflection of expected to be in the limit stated in code of practice.